PELATIHAN PENELITIAN TINDAKAN KELAS BAGI GURU-GURU SE KOTA MADYA PAYAKUMBUH - Darman, Regina Ade; Hutabri, Ellbert; Alfiriani, Adlia; Yusran, yusran; Mary, Thomson (ASOSIASI IDEBAHASA KEPRI, 2025)
Community service is one of the key pillars of the higher education tridharma, aimed at delivering tangible contributions to society through the application of academic expertise by university lecturers. In this community engagement activity, the primary targets are teachers in the Payakumbuh City area. Teachers are regarded as agents of change who play a pivotal role in fostering educational renewal through various innovations rooted in the evaluation and reflection of ongoing teaching and learning practices. A shift in the teacher’s paradigm can be observed through their ability to understand and address challenges in the learning process, which can be systematically implemented through Classroom Action Research (CAR). CAR is considered a highly relevant strategic approach for enhancing the quality of classroom instruction and, ultimately, for contributing to the broader improvement of educational standards. In this framework, teachers are not merely instructional facilitators but also reflective practitioners and designers of effective and adaptive learning strategies. Given the rapid advancements in the fields of Science, Technology, and the Arts (IPTEKS), the demand for higher-quality education continues to rise. Therefore, specialized training is essential to equip teachers with the necessary competencies to design and implement CAR effectively. Such training constitutes a strategic effort to strengthen teachers' professional capacities and to enhance the quality of education they provide.